Energy Policy and International Competitiveness - Grassini, Maurizio; Bardazzi, Rossella (Atti, 2009)
This book is a collection of selected papers presented at the XVI Inforum World Conference organized by the European University of Lefke, North Cyprus, in September 2008. Inforum (Interindustry Forecasting Project at the University of Maryland) was founded in 1967 by Dr. Clopper Almon, now Professor Emeritus at the University of Maryland. At international level, partners build national econometric models for their own country sharing a common modelling approach based on a sectoral representation of the economy. The contributions presented here illustrate the wide variety of issues that can be explored using these models, with particular emphasis on energy policies and competitiveness analyses, which are very high on the agenda of policymakers worldwide.